2009
DOI: 10.1016/j.cyto.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma and interleukin-4 single nucleotide gene polymorphisms in Paracoccidioidomycosis

Abstract: The gene polymorphisms interferon-gamma (IFN-gamma) +874 T/A and interleukin (IL)-4 -590 C/T have been associated with the altered production of cytokines. Therefore, they might be indicative of the occurrence of Paracoccidioidomycosis (PCM) caused by Paracoccidioides brasiliensis. The analysis of single nucleotide polymorphism (SNP) at position+874 IFN-gamma showed an increase occurrence of A/T genotype in both PCM patients and healthy individuals as control (HIC) (56% and 45%, respectively), while the alleli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…The SNP at the -183G>T position is related to increased transcription activity [26], whereas +874A>T is located in a region where the number of replicates can modulate the expression of messenger RNA and the production of cytokines [21, 72]. The T allele is associated with a high number of replicate copies and activates the transcription site for the NF- κ B pathway, which correlates with high cytokine expression [73, 74]. The AA, TA, and TT genotypes are associated with low, intermediate, and high production of IFN- γ , respectively [21, 75].…”
Section: Discussionmentioning
confidence: 99%
“…The SNP at the -183G>T position is related to increased transcription activity [26], whereas +874A>T is located in a region where the number of replicates can modulate the expression of messenger RNA and the production of cytokines [21, 72]. The T allele is associated with a high number of replicate copies and activates the transcription site for the NF- κ B pathway, which correlates with high cytokine expression [73, 74]. The AA, TA, and TT genotypes are associated with low, intermediate, and high production of IFN- γ , respectively [21, 75].…”
Section: Discussionmentioning
confidence: 99%
“…These data were derived from a patient cohort with acute leukemia and no data on cytokine levels are available. Another study revealed altered IL-4 levels in patients with paracoccidioidomycosis [67] . IL-13 is a cytokine that, among other functions, inhibits inflammatory cytokine production.…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…Resistance or mild manifestation of the disease has been related to IFN-γ and TNF-α production, while increased susceptibility to disease phenotypes are observed associated with a predominant production of Th2 interleukins IL-4, IL-5, IL-10 and IL-13. 80 Molecular genetic studies have shown evidence of association of PCM with specific variants of immune response-related genes. Specific alleles of the TNFA (-308) polymorphism were associated with PCM in a small case-control population sample from Brazil.…”
Section: Other Infectious Diseases Of Interest In Dermatology Paracocmentioning
confidence: 99%
“…For IL4, the susceptibility C/T genotype was associated with higher production of this cytokine. 80,81 Chromoblastomycosis Chromoblastomycosis is a chronic mycosis involving the skin and subcutaneous tissue. A large number of melanized (dematiaceous) fungi have been associated with the disease, the most common being Fonsecaea pedrosoi and Cladophialophora carrioni.…”
Section: Other Infectious Diseases Of Interest In Dermatology Paracocmentioning
confidence: 99%
See 1 more Smart Citation